Structural–functional brain changes in depressed patients during and after electroconvulsive therapy. Issue 1 (23rd November 2016) - Yrondi, Antoine; Péran, Patrice; Sauvaget, Anne; Schmitt, Laurent; Arbus, Christophe
Abstract : Objectives: Electroconvulsive therapy (ECT) is a non-pharmacological treatment that is effective in treating severe and treatment-resistant depression. Although the efficacy of ECT has been demonstrated to treat major depressive disorder (MDD), the brain mechanisms underlying this process remain unclear. Structural–functional changes occur with the use of ECT as a treatment for depression based on magnetic resonance imaging (MRI). For this reason, we have tried to identify the changes that were identified by MRI to try to clarify some operating mechanisms of ECT. We focus to brain changes on MRI [structural MRI (sMRI), functional MRI (fMRI) and diffusion tensor imging (DTI)] after ECT. Methods: A systematic search of the international literature was performed using the bibliographic search engines PubMed and Embase. The research focused on papers published up to 30 September 2015. The following Medical Subject Headings (MESH) terms were used: electroconvulsive therapy AND (MRI OR fMRI OR DTI). Papers published in English were included. Four authors searched the database using a predefined strategy to identify potentially eligible studies. Results: There were structural changes according to the sMRI performed before and after ECT treatment. These changes do not seem to be entirely due to oedema. This investigation assessed the functional network connectivity associated with the ECT response in MDD. ECT response reverses the relationship from negative to positive between the two pairs of networks. Conclusion: We found structural–functional changes in MRI post-ECT. Because of the currently limited MRI data on ECT in the literature, it is necessary to conduct further investigations using other MRI technology.